2008
DOI: 10.1021/ja8033763
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Mode of Action of Largazole: A Potent Class I Histone Deacetylase Inhibitor

Abstract: The efficient total synthesis of the recently described natural substance largazole (1) and it’s active metabolite largazole thiol (2) is described. The synthesis required eight linear steps and proceeded in 37% overall yield. It is demonstrated that largazole is a pro-drug, that is activated by removal of the octanoyl residue from the 3-hydroxy-7-mercaptohept-4-enoic acid moiety to generate the active metabolite largazole thiol (2) which is an extraordinarily potent Class I histone deacetylase inhibitor. Synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(214 citation statements)
references
References 31 publications
6
207
0
1
Order By: Relevance
“…The resulting N-terminal GFP-p27 fusion, detectable by fluorescence microscopy, was used to determine the levels of p27 expression upon treatment of cells with the compound libraries in 96-well format. Much to our surprise, the most potent hit that emerged from this screen was the natural compound Largazole (Figure 1), which was first described by Luesch and coworkers (15) and subsequently synthesized in several laboratories including ours (1,3,10,14,15,18,19). Largazole induced a robust and highly uniform upregulation of GFP-p27 at concentrations as low as 1 nM (Figure 2a) as compared to the expression levels after treatment with the proteasome inhibitor MG132.…”
Section: Resultsmentioning
confidence: 94%
“…The resulting N-terminal GFP-p27 fusion, detectable by fluorescence microscopy, was used to determine the levels of p27 expression upon treatment of cells with the compound libraries in 96-well format. Much to our surprise, the most potent hit that emerged from this screen was the natural compound Largazole (Figure 1), which was first described by Luesch and coworkers (15) and subsequently synthesized in several laboratories including ours (1,3,10,14,15,18,19). Largazole induced a robust and highly uniform upregulation of GFP-p27 at concentrations as low as 1 nM (Figure 2a) as compared to the expression levels after treatment with the proteasome inhibitor MG132.…”
Section: Resultsmentioning
confidence: 94%
“…Bowers and coworkers demonstrated that largazole is, in fact, a pro-drug, and largazole thiol (32) is its active form. 94 Their finding is supported by HDAC1, 2, 3, and 6 inhibitory activity data (K i , nM) of 0.07, 0.07, 0.17, and 25, respectively, for largazole thiol vs. 20, 21, 48, and 41000 for largazole.…”
Section: Natrual-products Hdacimentioning
confidence: 79%
“…exhibits in vitro and in vivo osteogenic activity by its histone deacetylases (HDACs) inhibition. Largazole is a 16 membered macrocycle possessing unusual structural features, includes a substituted 4-methylthiazoline linearly fused to a thiazole and a 3-hydroxy-7-mercaptohept-4-enoic acid unit (Bowers et al, 2008). Biological evaluation suggests that largazole and its key analogs are class I HDAC inhibitor.…”
Section: Marine Cyanobacteriamentioning
confidence: 99%